Inter-agency information sharing coordination on humanitarian logistics support for urban disaster management in Kuala Lumpur - Mohammed Zain, Ruzaidin; Mohd Zahari, Haliza; Mohd Zainol, Noor Azmi (Frontiers in Sustainable Cities, 2023)
Information sharing is critical in establishing coordinated and effective decision-making processes for a humanitarian logistical response. Better coordination and decision-making will lead to a better response for beneficiaries as a result of timely and high-quality information reaching more humanitarian actors. However, sharing this information between actors is a challenge, especially in coordinating logistics response during an urban disaster, due to the sheer scale of potential impacts and risks on human lives and the economy. This research explored the current humanitarian logistics settings and identified issues and challenges of inter-agency information sharing coordination on humanitarian logistics support for urban disasters in Kuala Lumpur. Focus Group Discussion was conducted with participants from six government agencies that are responsible for providing humanitarian logistics support for urban disasters in Kuala Lumpur. This study also examined existing disaster management directives and the agency’s Standard Operating Procedures (SOPs). The findings revealed issues with information redundancy, lack of tools to manage and distribute information, and coordination issues among agencies in providing knowledge sharing and managing real-time information during a disaster. A review of existing policies and formulation of clear guidelines are needed to address the issues and improve the overall humanitarian logistics support coordination.